Critical Discourse Analysis 0n Ideology 0f Feminism in Nawāl Al-Sa’adāwi’s Mudzakkirāt Thobībah - Karlina Helmanita; Emzir Emzir; Zainal Rafli (JETL (Journal of Education, Teaching and Learning), 2018)
The aim of this research is to carry out a critical discourse analysis on the ideology of feminism  in the novel  Mudzakkirāt Thobībah by Nawāl Al-Sa’adāwī, through linguistic feature in the symbol of sound, vocabulary and text structure or the dialog contained in the novel. This research utilizes qualitative approach with content analysis method of Philipp Mayring. Data is collected by way of reading the novel, identifying, marking, classifying and interpreting meaning. The findings are 1) patriarchal sound symbols because of the existence of  non (nir)-sound in Nawāl Al-Sa’adāwī’s Mudzakkirāt Thobībah linguistic feature. They can be identified as patriarchal because the text is commonly read by men due to minimum access of education for women. Women are illiterate and experience oppression in education. There is almost no information about women figure that become a linguist, scientists and including female scholars. 2) the inequality of antonym and synonym. The word relation and series word by word (word) is ideologically unequal. The words that are used for women are not culturally conditioned as a partner to men. 3) The hegemony of power in the structure of texts in the form of dialog among the characters. In the texts the harmonious and disharmonious dialogs are reciprocal. From the result of this research, the researchers recommend a newly designed curriculum for education to carry out advocacy for the awareness linguistic feminist education with the character of the East and Indonesia.